2022
DOI: 10.1136/rmdopen-2021-002063
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection among patients with autoinflammatory diseases: a study on 117 French patients compared with 1545 from the French RMD COVID-19 cohort: COVIMAI – the French cohort study of SARS-CoV-2 infection in patient with systemic autoinflammatory diseases

Abstract: ObjectiveThere is little known about SARS-CoV-2 infection in patients with systemic autoinflammatory disease (SAID). This study aimed to describe epidemiological features associated with severe disease form and death. Mortality between patients with and without SAID hospitalised for SARS-CoV-2 infection was compared.MethodsA national multicentric prospective cohort study was conducted from the French Rheumatic and Musculoskeletal Diseases (RMD) COVID-19 cohort. Patients with SAID were matched with patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…1) However, previous population cohort and survey-based studies reported that both adult and pediatric patients with rheumatologic diseases are not at higher risk of severe COVID-19 or worse outcomes versus the general population. 30,31) In an Italian pediatric study conducted early in the pandemic, only 8 of 123 children treated with biological disease-modifying antirheumatic drugs (bDMARDs) had mild respiratory symptoms. 33) No patient required the interruption of ongoing therapy or hospitalization.…”
Section: Covid-19 In Immunosuppressed Children With Rheumatologic Dis...mentioning
confidence: 99%
See 2 more Smart Citations
“…1) However, previous population cohort and survey-based studies reported that both adult and pediatric patients with rheumatologic diseases are not at higher risk of severe COVID-19 or worse outcomes versus the general population. 30,31) In an Italian pediatric study conducted early in the pandemic, only 8 of 123 children treated with biological disease-modifying antirheumatic drugs (bDMARDs) had mild respiratory symptoms. 33) No patient required the interruption of ongoing therapy or hospitalization.…”
Section: Covid-19 In Immunosuppressed Children With Rheumatologic Dis...mentioning
confidence: 99%
“…Previous studies of pediatric rheumatology patients reported low severe COVID-19 and mortality rates, but the literature is less extensive for these diseases and continuous monitoring is needed. [30][31][32][33][34][35][36][37] Furthermore, these patients experienced a lack of medical access and treatment interruptions during the COVID-19 pandemic, which might have led to the progression of their underlying rheumatologic diseases. 8,9) Therefore, it is important to keep the underlying disease under control by maintaining treatment during the pandemic.…”
Section: Covid-19 In Immunosuppressed Children With Rheumatologic Dis...mentioning
confidence: 99%
See 1 more Smart Citation
“…A few other cohorts have shown increased risk of death for patients with vasculitis, but the data are scarce and lack power ( 44 ). Additionally, in another cohort, the risk of severe COVID-19 was not higher in auto-inflammatory patients than in patients with other rheumatic conditions ( 45 ) or in the general population ( 46 ).…”
Section: Discussionmentioning
confidence: 81%
“…In sarcoidosis, two studies suggested that this association could be explained by ILD due to the disease, (41), with a specific increased risk of hospitalization in patients with stage III sarcoidosis (5,42). Other underpowered cohorts did not identify sarcoidosis as a risk factor of severe 43). Regarding vasculitis, in the absence of control populations, only few studies analyzed the risk of COVID severity associated with the vasculitis itself.…”
Section: Discussionmentioning
confidence: 99%